BLAST-FURNACE ANALYS WAY OF EVIDENTIAL CONSTRUCTION OF INDUSTRY EDUCATIONAL STANDARDS - Сидоров, М. О.; Мендзебровський, І. Б.; Малін, І. В. (Science-based technologies, 2009)
The article presents results of a study in which returned the established model of blast field of education experts as "Software Engineering", as well as a template for building other educational standards, which can be implemented as an automated expert system.To build the educational standards of any industry the system will be universal if the formulation of relevant entities substituted, namely, models, components, language.